Secondary Bile Acids and Tumorigenesis in Colorectal Cancer - Liu, Yujing; Zhang, Shengan; Zhou, Wenjun; Hu, Dan; Xu, Hanchen; Ji, Guang (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the most common and deadly cancers in the world and is a typical inflammatory tumor. In recent years, the incidence of colorectal cancer has been increasing year by year. There is evidence that the intake of high-fat diet and overweight are associated with the incidence of colorectal cancer, among which bile acids play a key role in the pathogenesis of the disease. Studies on the relationship between bile acid metabolism and the occurrence of colorectal cancer have gradually become a hot topic, improving the understanding of metabolic factors in the etiology of colorectal cancer. In this review, the classification of bile acids and their role in promoting the occurrence of colorectal cancer are discussed, and we highlights how a high-fat diet affects bile acid metabolism and destroys the integrity of the intestinal barrier.